Comparison of Housing Practices Followed by Goat Farmers Under Stall Fed and Extensive Rearing System in Punjab - Dhaliwal, Aman Deep Singh; Kasrija, Rajesh; Singh, Parminder; Jadoun, Y. S. (International Journal of Livestock Research, 2021)
The present study was conducted in all the six different agro-climatic zones of Punjab to compare the housing knowledge level of goat farmers following stall feeding and extensive rearing system. A total of 120 goat farmers, belonging to Group I (Stall fed, n=60) and Group II (extensive rearing, n=60) were randomly selected (10 goat farmers each for Group I and Group II from every zone). The goat farmers were personally interviewed with the help of interview schedule. The mean housing awareness percentage in Zone I, II, III, IV, V, VI and Overall Punjab was reported to be 32.33%, 28.00%, 37.33%, 31.33%, 44.00%, 21.00% and 33.27% respectively. There is significant difference (P < 0.05) for housing practices between different zones of Punjab. Group I had more awareness (P < 0.01) about different housing practices than Group II goat farmers. The housing knowledge level of Group I and Group II goat farmer in Punjab was medium and low respectively. The present study suggests need of organizing more extension activities regarding knowledge enrichment of goat farmers for housing practices after assessing knowledge level of goat farmer belonging to a particular area/zone.